Understanding Writing Challenges and Performance among First-Year Military Students: A Study at Ethiopian Defense University - Alemu, Abebe; Gebremariam, Alamirew (Universitas Muhammadiyah Barru, 2025)
The main objective of this study was to investigate students’ writing challenges and performance at Ethiopian Defense University/EDU/. For the study, the researcher used an explanatory sequential mixed method design. English language instructors and first-year students of EDU provided data for the study. Particularly, first-year students of the university's colleges of Engineering and Resource Management produced the replies. The researcher used a questionnaire to determine students’ writing challenges, a paragraph writing test to determine their level of writing performance, and interviews with first-year students and English language instructors. Therefore, 108 students completed the questionnaire and took writing test. As a consequence, 8 students and 6 English language instructors were interviewed. According to the study's findings, the main writing challenges that students encountered were: insufficient linguistic background, a lack of writing practices, traumatic past experiences, a lack of writing motivation, carelessness in writing, scarcity of resources, shortage of time, and unsupportive English courses and modules. Additionally, the findings of the correlation analysis showed that the association between the students’ writing challenges and writing performance is statistically insignificant. Lastly, it was proposed that bridging English language trainings, revisions to English courses and course modules, and increased awareness of traumatic experience on writing among the university community could all help improve students' writing performance.